The Tendency of People to Switch from Traditional Banks to PSPs Such as Revolut - Sarcanean, Grigore (2025)
The aim of this thesis is to critically analyze and discuss the increasingly visible trend of consumers drifting away from traditional banks to modern Payment Service Providers (PSPs) like Revolut. The study aims to explore key drivers behind this shift and encompass aspects such as convenience, affordability, innovation in technological progress, and certain regulatory changes influencing consumer requirements and desires. The hypothesis is that digitalization of financial services, along with consumer desire for flexibility and reduced fees, has been a major factor in the rising popularity of PSPs over conventional banks. This thesis contributes to the discussion of the future of banking by analyzing consumer behavior trends, regulatory evolution, and relative strengths of PSPs over traditional banks. The identification of the main drivers of this movement will be helpful in providing insight into the future of financial services and the potential pitfalls traditional banks will face in retaining customers.The theoretical part will cover literature review covering various aspects of financial technology, the transformation occurring in the banking industry and research on consumer behavior, will examine how various elements, including the cost of transactions, general user experience, the concept of financial inclusion, and the level of trust that consumers place in digital platforms, play a vital role in shaping and influencing consumer choices in the fast-evolving financial landscape of today. It will also have models that outline how traditional banking networks are shifting to decentralized financial services, how PSPs leverage technology to enhance customer satisfaction and ease of financial transactions. The empirical part will employ a survey-based model combined with a regression model to quantify the determinants of consumer adoption of PSPs compared to traditional banks.